Parental awareness of oral health in children with epidermolysis bullosa in Indonesia - Azzahra, Rissa Shabira; Dwiyana, Reiva Farah; Diana, Inne Arline; Setiawan, Arlette Suzy (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Children affected by epidermolysis bullosa (EB) have serious oral conditions that may affect their quality of life. It is the parents’ crucial role to maintain the oral health of children with EB. Purpose: This study aims to determine the crucial role of parents in maintaining the oral health of children with EB. It also aims to assess parents’ oral health knowledge and perceptions of their children’s oral health-related quality of life. Methods: Conducted at Yayasan Dystrophic Epidermolysis Bullosa Research Association, Indonesia, this descriptive study employed a questionnaire translated through cross-cultural adaptation and the Caregiver Perception Questionnaire using a Likert scale. Results: Among the 18 respondents, parental knowledge appeared favorable. Regarding the oral symptoms dimension, 56% of children were in the excellent category, 28% in the moderate category, and 17% in the poor category. In terms of functional limitations, 50% were in the suitable category, 39% were moderate, and 11% were poor. In the emotional state dimension, 78% of participants were in the excellent category, whereas 22% were in the moderate category. In the social conditions dimension, 89% were in the excellent category and 11% in the moderate category. Conclusion: Although parents demonstrated an understanding of oral health care for EB, challenges in implementation emerged.